2009
DOI: 10.1091/mbc.e08-03-0308
|View full text |Cite
|
Sign up to set email alerts
|

The E3 Ubiquitin Ligase Atrophin Interacting Protein 4 Binds Directly To The Chemokine Receptor CXCR4 Via a Novel WW Domain-mediated Interaction

Abstract: The E3 ubiquitin ligase atrophin interacting protein 4 (AIP4) mediates ubiquitination and down-regulation of the chemokine receptor CXCR4. AIP4 belongs to the Nedd4-like homologous to E6-AP carboxy terminus domain family of E3 ubiquitin ligases, which typically bind proline-rich motifs within target proteins via the WW domains. The intracellular domains of CXCR4 lack canonical WW domain binding motifs; thus, whether AIP4 is targeted to CXCR4 directly or indirectly via an adaptor protein remains unknown. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
131
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(136 citation statements)
references
References 45 publications
4
131
1
Order By: Relevance
“…Most Nedd4-2-targeted proteins interact with its WW3-4 domains. Interestingly, our study revealed that the N-terminal region of TRPV6 interacts with WW1 and WW2 domains, a situation similar to the interaction between CXCR4 and AIP4 (44). However, the interaction between WW1-2 domains and TRPV6 is not indispensable for the association between Nedd4-2 and TRPV6, because other domains, such as the HECT and C2 domains, significantly interact with the TRPV6 C-terminal region.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Most Nedd4-2-targeted proteins interact with its WW3-4 domains. Interestingly, our study revealed that the N-terminal region of TRPV6 interacts with WW1 and WW2 domains, a situation similar to the interaction between CXCR4 and AIP4 (44). However, the interaction between WW1-2 domains and TRPV6 is not indispensable for the association between Nedd4-2 and TRPV6, because other domains, such as the HECT and C2 domains, significantly interact with the TRPV6 C-terminal region.…”
Section: Discussionmentioning
confidence: 48%
“…However, not every protein directly binds with the WW domain of Nedd4-type ubiquitin E3 ligases through a PY motif. A chemokine receptor, CXCR4, which has no PY motif, binds with the WW1 or WW2 domains of E3 ubiquitin ligase AIP4 via a 324/ 325 double serine in its C-terminal region (44). PTEN even interacts with the C2 and HECT domains of Nedd4 (45).…”
Section: Discussionmentioning
confidence: 99%
“…The modulation of the p63-Itch binding by phosphorylation could be a mechanism more widespread and regulate also the interaction of Itch-E3 ligase with other proteins, such as observed in the interaction of Itch with the chemokine receptor CXCR4. 111 This last one occurs through WW-Itch domains and a phosphorylated serine residue of a recognition sequence that does not contain proline residues. 111 The scheme in Figure 7 can be generalized for other PY interactions with WW domains, as the PY motif of p63, is also present in other proteins including for example RASSF5 where the PPxY motif interact with the WW domain of Itch 112 in a manner very similar to p63.…”
Section: Discussionmentioning
confidence: 99%
“…111 This last one occurs through WW-Itch domains and a phosphorylated serine residue of a recognition sequence that does not contain proline residues. 111 The scheme in Figure 7 can be generalized for other PY interactions with WW domains, as the PY motif of p63, is also present in other proteins including for example RASSF5 where the PPxY motif interact with the WW domain of Itch 112 in a manner very similar to p63. All these proteins are characterized by the nearby presence of a (T/S)P motif, which is a potential recognition site of the WW domain of the IV group present in the prolyl-isomerase Pin1.…”
Section: Discussionmentioning
confidence: 99%
“…CXCR4 mediated chemotaxis along a gradient of its cognate ligand, stromal-derived factor 1␣ (SDF-1␣/CXCL12), and supports metastasis of cancer to the bone marrow (25,28). Ligand-induced lysosomal degradation of CXCR4 is critical for downstream signal attenuation and is mediated by the HECT family E3 ligase atrophininteracting protein 4 (AIP4/Itch) (29,30) and deubiquitinase ubiquitin-specific protease 14 (USP14) (31). CXCR4 activation has also been linked to ubiquitination of Hrs by AIP4, and its trafficking proceeds along an Hrs-dependent pathway (32), suggesting that alteration in the Hrs ubiquitination status may modulate CXCR4 turnover.…”
mentioning
confidence: 99%